The Time, The Residence, The Person Who Dwells It, The Knowledge Born from the Suspended:: New Senses of Freedom and (Re) Creation in Learning to Own - Santos, Renata Aparecida Felinto (Revista Vazantes, 2020)
Timelessness. Artist report.